Criteria for safe return to sports activity after myocarditis: An analysis of clinical practice - Gólcz, Julia; Bursztyn, Michał; Szaryński, Mikołaj; Sikorski, Adam; Kadłubowska, Karolina; Jakubowska, Paulina; Chojnowska, Natalia; Rytel, Jan; Jakubowska, Martyna; Gólcz, Adrian; et al. (Quality in Sport, 2026)
<article class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" tabindex="-1" data-turn-id="request-WEB:5b8bb194-fb01-4291-8953-adec29f501c1-2" data-testid="conversation-turn-6" data-scroll-anchor="true" data-turn="assistant"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-1" dir="auto" data-message-author-role="assistant" data-message-id="6e316c3e-013e-4ae7-8b80-54a69d992c9a" data-message-model-slug="gpt-5-2"> Myocarditis is an inflammatory disease of the myocardium that can lead to ventricular dysfunction, arrhythmias, and sudden cardiac death, particularly in athletes. The 2025 ESC Guidelines emphasize that premature return to intense exercise increases the risk of persistent inflammation, inflammatory cardiomyopathy, and malignant arrhythmias. This review summarizes current evidence and recommendations on diagnosis, rehabilitation, and return-to-sport decisions after myocarditis, focusing on athletes and the 2025 ESC guidelines. A narrative review of major guidelines and recent studies on biomarkers, imaging, athlete-specific risk, COVID-19–related myocarditis, and rehabilitation strategies was performed, selecting evidence relevant to risk stratification and safe exercise resumption. Diagnosis combines clinical findings with biomarkers (troponins, CRP, BNP/NT-proBNP). Echocardiography assesses ventricular function, while CMR remains the gold standard for tissue characterization and fibrosis detection (LGE). Rehabilitation should begin after symptom stabilization, biomarker normalization, and ventricular recovery, progressing gradually under supervision. Return to sport requires complete symptom resolution, normal function and biomarkers, and absence of significant arrhythmias. Repeat CMR is recommended if previous imaging showed edema or fibrosis. Athletes with extensive LGE or persistent dysfunction should avoid moderate-to-high-intensity activity due to high arrhythmic risk. Post-myocarditis management, especially in athletes, demands comprehensive evaluation, structured rehabilitation, and strict return-to-play criteria. The 2025 ESC guidelines stress individualized decisions based on biomarkers, ECG/Holter, and CMR to ensure safety.